STEP EARLY AND TREAT: SOLUTIONS FOR REDUCING DATA BREACHES WITH CORPORATE SOCIAL RESPONSIBILITY AS TWO COMPLEXING LAYERS OF PROTECTION - Budi Raharja, Arif; Novianha Pynatih, Ngurah Made; Aripin, Zaenal (Yayasan Kreatif Indonesia Emas, 2024)
The increased use of information technology has brought great benefits to modern organizations, but has also increased the risk of data breaches. In facing these challenges, the Go Early and Cure approach has been proposed as a complementary strategy to reduce the risk of data breaches. The Go First approach emphasizes prevention before a data breach occurs, while the Treat approach focuses on rapid response after a data breach occurs. Corporate Social Responsibility (CSR) also plays an important role in supporting both approaches by raising awareness, strengthening data protection and improving relationships with external stakeholders. However, implementing both approaches faces a number of challenges, including a corporate culture that may not support data security practices, limited resource availability, and varying data security awareness among organizational members. To overcome these challenges, organizations need to prioritize building a culture that supports data security, allocate resources efficiently, and continuously increase awareness of cyber security risks. By addressing these challenges, organizations can strengthen their layers of protection against data breaches and maintain stakeholder trust.